Pengaruh Harga dan Citra Perusahaan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Giant Kota Semarang) - Nimas Kartika Dewastuti; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2017)
The development of Indonesian people's lifestyle changes every year. Business sector is one of them, a business that grows rapidly and significantly causes the mindset of the people of Indonesia mengingnkan everything practical, including in the fulfillment of life needs. People are beginning to shift from traditional retail to cleaner and more comfortable modern retailers. One of the existing retail companies in Indonesia is Giant that offers a wide range of daily necessities products.This type of research is explanatory research, with a population of 100 respondents who have visited and made a purchase at Giant Semarang City. Sampling in this study using non-probability sampling. The sampling technique uses accidental sampling. Data were collected through questionnaires. The data analysis method used using Generalized Structured Component Analysis (GeSCA).Based on the results of GeSCA calculation analysis can be explained that the results of direct impact test on this research model showed the results of positive and significant influence. The result of indirect effect test on the model also shows the result of positive and significant influence. The effect of customer satisfaction as a mediator variable in the model is partial and perfect mediation.Based on that, the researcher suggested that Giant Semarang City to increase Price and Corporate Image by reviewing the standard of the mean value of each variable is still below the average value.